Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's solve the problem step by step:
### Step 1: Define the Equations
We need to find two integers, \(a\) and \(b\), such that:
1. Their sum is \(-3\):
[tex]\[ a + b = -3 \][/tex]
2. Their difference is \(-5\):
[tex]\[ a - b = -5 \][/tex]
### Step 2: Solve the System of Equations
We have the following system of linear equations from the given conditions:
1. \( a + b = -3 \)
2. \( a - b = -5 \)
First, let's add these two equations together:
[tex]\[ (a + b) + (a - b) = -3 + (-5) \][/tex]
This simplifies to:
[tex]\[ 2a = -8 \][/tex]
[tex]\[ a = -4 \][/tex]
### Step 3: Substitute the Value of \(a\)
Now, we take the value of \(a\) and substitute it back into the first equation (\(a + b = -3\)):
[tex]\[ -4 + b = -3 \][/tex]
[tex]\[ b = -3 + 4 \][/tex]
[tex]\[ b = 1 \][/tex]
### Step 4: Verify the Solution
We found two integers, \(a = -4\) and \(b = 1\). Let's verify if they satisfy both conditions:
1. Sum is \(-3\):
[tex]\[ -4 + 1 = -3 \][/tex]
2. Difference is \(-5\):
[tex]\[ -4 - 1 = -5 \][/tex]
### Step 5: Address the Additional Condition
While the third condition (\(a - b = 2\)) appears in the text, we don't need it to solve the primary conditions of sum and difference provided. The correct integers satisfying the sum \(-3\) and difference \(-5\) are \(a = -4\) and \(b = 1\).
The pair of integers meeting the given conditions are:
[tex]\[ (-4, 1) \][/tex]
### Step 1: Define the Equations
We need to find two integers, \(a\) and \(b\), such that:
1. Their sum is \(-3\):
[tex]\[ a + b = -3 \][/tex]
2. Their difference is \(-5\):
[tex]\[ a - b = -5 \][/tex]
### Step 2: Solve the System of Equations
We have the following system of linear equations from the given conditions:
1. \( a + b = -3 \)
2. \( a - b = -5 \)
First, let's add these two equations together:
[tex]\[ (a + b) + (a - b) = -3 + (-5) \][/tex]
This simplifies to:
[tex]\[ 2a = -8 \][/tex]
[tex]\[ a = -4 \][/tex]
### Step 3: Substitute the Value of \(a\)
Now, we take the value of \(a\) and substitute it back into the first equation (\(a + b = -3\)):
[tex]\[ -4 + b = -3 \][/tex]
[tex]\[ b = -3 + 4 \][/tex]
[tex]\[ b = 1 \][/tex]
### Step 4: Verify the Solution
We found two integers, \(a = -4\) and \(b = 1\). Let's verify if they satisfy both conditions:
1. Sum is \(-3\):
[tex]\[ -4 + 1 = -3 \][/tex]
2. Difference is \(-5\):
[tex]\[ -4 - 1 = -5 \][/tex]
### Step 5: Address the Additional Condition
While the third condition (\(a - b = 2\)) appears in the text, we don't need it to solve the primary conditions of sum and difference provided. The correct integers satisfying the sum \(-3\) and difference \(-5\) are \(a = -4\) and \(b = 1\).
The pair of integers meeting the given conditions are:
[tex]\[ (-4, 1) \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.